2017
DOI: 10.1017/s174217051700014x
|View full text |Cite
|
Sign up to set email alerts
|

Social, economic and environmental impacts of organic cotton production on the livelihood of smallholder farmers in Odisha, India

Abstract: Cotton is an important source of income for smallholder farmers in India, usually grown very intensively. To counteract negative impacts of cotton cultivation in India, such as environmental degradation and financial dependency due to high input costs, organic cotton cultivation is being promoted by non-governmental organizations in the country. This study examines how the conversion to organic cotton cultivation influences the livelihood of smallholder farmers in rural India. Interviews with organic farmers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 41 publications
1
41
0
Order By: Relevance
“…In many Asian countries such as Pakistan, mobile banking is taking off and has already become one of the "new and fast-developing spaces at the convergence of technology and financial services"' [78]. It saves from the exploitative behavior of the middle-men, who use the prevailing information gap and claim a relatively high interest rate [19,79]. ICT will improve the creditworthiness of smallholders, thereby strengthening the partnerships among value chain actors that reduce the cost of interaction among stakeholders and the risk associated with VCF [80,81].…”
Section: Information and Communication Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…In many Asian countries such as Pakistan, mobile banking is taking off and has already become one of the "new and fast-developing spaces at the convergence of technology and financial services"' [78]. It saves from the exploitative behavior of the middle-men, who use the prevailing information gap and claim a relatively high interest rate [19,79]. ICT will improve the creditworthiness of smallholders, thereby strengthening the partnerships among value chain actors that reduce the cost of interaction among stakeholders and the risk associated with VCF [80,81].…”
Section: Information and Communication Technologymentioning
confidence: 99%
“…As a result, financial services of banks are very limited to organic producers and it is very difficult for smallholders to get loans [16,17]. In addition, the rural low-income smallholders have little formal relationship with the banking system; this makes them dependent on arthi (middlemen) for informal loans, who charge predatory prices for loans because of their low creditworthiness [18,19]. According to Haq et al [20] and Altenbuchner et al [19] arthi appears to be a service provider fulfilling the financial needs of farmers in rural areas where the formal financial sector is not considered creditworthy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially in areas such as horticulture, growers are increasingly converting to certified organic agriculture, and name water security, finance, and environmental issues as their main motivations for conversion [11]. Some other potential benefits and costs of organic agriculture include reduced input costs, poverty reduction, and improved soil conditions [36,37]; higher income (especially in dry years) [38,39]; and more diversified production and resilience [39,40]. In South Australia, it has been found that organic and biodynamic grape growers perceive less vulnerability to reduced water and greater resilience to water stress due to their higher soil water retention and carbon matter in soils [11].…”
Section: Potential Influence Of Organic Farming On Mental Healthmentioning
confidence: 99%
“…The main objectives of organic farming are to enhance farmers' livelihoods, increase agricultural 30 production within the less privileged group and also reduce the negative impact of inorganic 31 fertilizers on the environment (Scialabba and Hattam, 2002). Altenbuchner et al (2017) further 32 mentioned that the goal of organic farming also includes women empowerment with the aim of 33 gaining access to education thereby assisting them to make informed decision that may affect their 34 health and overall wellbeing. Through the introduction of organic farming, it is also possible for 35 women to apply their indigenous knowledge and embrace their role as 'keeper of seeds' which in 36 turn encourages biodiversity (Farnworth & Hutchings, 2009).…”
Section: Introduction 22mentioning
confidence: 99%